The changing face of major trauma in the UK. Issue 12 (23rd November 2015) - Kehoe, A; Smith, J E; Edwards, A; Yates, D; Lecky, F
Abstract : Aim: Major trauma (MT) has traditionally been viewed as a disease of young men caused by high-energy transfer mechanisms of injury, which has been reflected in the configuration of MT services. With ageing populations in Western societies, it is anticipated that the elderly will comprise an increasing proportion of the MT workload. The aim of this study was to describe changes in the demographics of MT in a developed Western health system over the last 20 years. Methods: The Trauma Audit Research Network (TARN) database was interrogated to identify all cases of MT (injury severity score >15) between 1990 and the end of 2013. Age at presentation, gender, mechanism of injury and use of CT were recorded. For convenience, cases were categorised by age groups of 25 years and by common mechanisms of injury. Longitudinal changes each year were recorded. Results: Profound changes in the demographics of recorded MT were observed. In 1990, the mean age of MT patients within the TARN database was 36.1, the largest age group suffering MT was 0–24 years (39.3%), the most common causative mechanism was road traffic collision (59.1%), 72.7% were male and 33.6% underwent CT. By 2013, mean age had increased to 53.8 years, the single largest age group was 25–50 years (27.1%), closely followed by those >75 years (26.9%), the most common mechanism was low falls (39.1%), 68.3% were male and 86.8% underwent CT. Conclusions: This study suggests that the MT population identified in the UK is becoming more elderly, and the predominant mechanism that precipitates MT is a fall from <2 m. Significant improvements in outcomes from MT may be expected if services targeting the specific needs of the elderly are developed within MT centres.